Severity Assessment and Immediate Outcome of Hospitalized Bronchiolitis Patient in a Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Bronchiolitis is the most common reason for hospitalization during infancy, being a burden for the children and family and bearing huge costs for the health care system. No formal scoring system is used in our country to assess the severity of bronchiolitis. This study will contribute to create referral knowledge about bronchiolitis among the health care providers of the community.Materials and methods: This cross-sectional observational study was carried out at the Department of the Paediatrics, Chittagong Medical College in 100  admitted patient with bronchilitis aged 1 month to 24 months. Respiratory rate, chest wall indrawing, nasal flaring, grunting, feeding ability, cyanosis and general behavior were used to measure severity. Outcome measurement parameters were duration of hospital stay, needs ICU support, needs mechanical ventilation, death and leave against medical advice.Results: Out of 100 patients, 52 patients had mild bronchiolitis, 31 had moderate and 17% had severe bronchiolitis. The average hospital stay for patients with mild bronchiolitis was 2.48 (±1.08) days.  4.53 ((±1.15) days for moderate bronchiolitis and for severe bronchiolitis it was 7.41 ( (±2.01) days. 15% of patients with severe bronchiolitis required ICU assistance and received CPAP or humidified oxygen. There was no death but 2% patient left against medical advice.Conclusion: This study concluded that most of the bronchiolitis patients admitted with a mild disease which could be treated at home with adequate counselling and assurance of parents. This will reduce the hospital burden and the financial cost to parents. At the same time referral criteria should be strengthened to start prompt treatment of patients with severe diagnosis.JCMCTA 2024 ; 35 (1) : 33-37